(untitled) (CIPEEX, 2022)
IN BRAZIL, VIOLENCE IS ONE OF THE BIGGEST PROBLEMS FACING THE BRAZILIAN POPULATION. ACCORDING TOUN DATA FROM THE SECRETARIAT FOR HUMAN RIGHTS (SDH), APPROXIMATELY ONE WOMAN EVERY 15SECONDS, AN ELDERLY PERSON EVERY 10 MINUTES, AND 18,000 CHILDREN A DAY ARE VICTIMS OF SOMETYPE OF VIOLENCE IN THE COUNTRY. IN THE FIRST HALF OF 2018, ACCORDING TO FEDERAL GOVERNMENT DATA, LIGUE 180 RECORDED 27 FEMICIDES, 51 HOMICIDES, 547 ATTEMPTED FEMICIDES, AND 118 ATTEMPTED MURDERS. OF THE REPORTS THAT ARRIVED, 37,396 WERE OF PHYSICAL VIOLENCE, AND 26,527 WERE OF PSYCHOLOGICAL VIOLENCE. ACCORDING TO A 2019 STUDY BY INSTITUTO LOCOMOTIVA AND INSTITUTO PATRCIA GALVO, 97% OF BRAZILIAN WOMEN HAVE ALREADY SUFFERED SOME TYPE OF HARASSMENT IN PUBLIC AND PRIVATE TRANSPORT IN BRAZIL. IN VIEW OF THIS, IT IS PROPOSED TO MAP, AND INFORM LEGAL DETERMINATIONS OF DISTANCE FROM THE AGGRESSOR TO VICTIMS OF DOMESTIC VIOLENCE AND DENOUNCE POSSIBLE VIOLATIONS OF THESE DETERMINATIONS, TRACING A PROFILE OF THE AGGRESSOR, PUBLICIZING HIS CONDUCT BEFORE THE DETERMINATIONS AND THUS STRENGTHENING LEGAL COMPLIANCE AND SAFETY OF THE VICTIM. BY CREATING A MEANS OF DISCLOSING LEGAL DOCUMENTS, WHERE COMPANIES AND PUBLIC AND PRIVATE INSTITUTIONS CAN CARRY OUT RESEARCH THAT FACILITATES THE RECOGNITION OF INDIVIDUALS WHO HAVE ENACTED PROTECTIVE MEASURES AND THUS AVOID THE OCCURRENCE OF FUTURE CASES IN THE PROFESSIONAL ENVIRONMENT AND STRENGTHEN THE SECURITY OF WOMEN. DURING THE PROJECT DEVELOPMENT PROCESS, AGILE METHODOLOGIES WERE USED TO APPROACH CONCEPTS OF SCRUM, DESIGN SPRINT, AND LEAN INCEPTION. WEEKLY IDEABRAINSTORMING WAS CONDUCTED TO DISCOVER NEW REQUIREMENTS FOR THE PRODUCT. THE DEVELOPMENT OF THE SYSTEM TOOK PLACE THROUGHOUT THE WEEK, WITH DELIVERIES AND VALIDATIONS BASED ON TIMELINES DEFINED WEEKLY. THE RESULTS OBTAINED WERE THE DEVELOPMENT OF ARTIFACTS SUCH AS A PROJECT OVERVIEW DOCUMENT, ACTIVITY BACKLOG, DESIGN, AND USER EXPERIENCE PLAN (PERSONA, USER JOURNEY DEVELOPMENT, AND PROTOTYPING) SOFTWARE ARCHITECTURE PLAN, INTEGRATION PLAN CONTINUOUS, VERIFICATION AND VALIDATION, AS WELL AS DATABASE MODELING AND DEFINITION. THE OBJECTIVE IS TO CREATE WEB SOFTWARE TO HELP DISSEMINATE AND MONITOR PROTECTIVE MEASURES USING THE MULTIDISCIPLINARY CONCEPTS TAUGHT IN SOFTWARE ENGINEERING BACHELOR’S DEGREE FOR CREATING ARTIFACTS, PROJECT MANAGEMENT, AND COMMUNICATION.